Upaya Melibatkan Masyarakat Sekitar Desa Pantai Cermin dalam Bidang Kesejahteraan Melalui Pemanfaatan Antibiotik - Frengki Candra Kusuma (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2022)
What if one day antibiotics are no longer effective against bacteria? This is really worrying, considering that until now it has become the mainstay of the treatment of various diseases caused by bacteria. A review of antibiotic use in developing countries by Radyowijati and Haak reported to people that antibiotics are “miracle drugs” or “virtues” that can prevent or treat various diseases or symptoms. Pantai Cermin Village is one of the villages in Sangir Bntang Hari Subdistrict, Solok-Selatan Regency. The method of implementing the activity is face-to-face counseling and providing information directly to the people of Pantai Cermin village, which is expected to be more effective than outreach actions through mass media or leaflets. This step is completed by using an expansion strategy. The things that need to be prepared are: a) Availability of tools to identify the companion group b) office status c) Greetings of service d) Preparation of information documents by the moderator group e) Understand the implementation time. Antibiotics as a treatment When bacteria multiply and produce symptoms of disease, your immune system is actually already on your body's antibodies start trying to destroy it to stop the growth of bacteria,How to take antibiotics properly It is important to understand that although drugs are very beneficial, they should not be taken lightly . , Antibiotics as prevention In addition, antibiotics should not be taken during pregnancy, people who are at high risk of infection can receive this drug as a preventive measure in the medical world, this is called prophylaxis. Anti-infective/antibiotic group These drugs consist of many types, but their antitoxin properties can be divided into six groups. Thus we can emphasize that the recommendation to use antibiotics has led to an increase in public knowledge, especially housewives, pregnant women, and people who have other diseases that are not caused by bacteria in the village of Pantai Cermin about using antibiotics, and be wise in using the right antibiotics. It is hoped that in the future health workers will often monitor the circulation of antibiotics and educate the people of Pantai Cermin village about the dangers of antibiotic abuse.